Hepatitis C and HIV Primary Care Screening Intervention Increases Identification and Linkage to Care within a Large Healthcare system. (4th October 2017) - Leonard, Michael; Mohanan, Sveta; Ludden, Thomas; Shade, Lindsay; Thomas, Jeremy; Tapp, Hazel
Abstract: Background: Societal and economic burdens of hepatitis C virus (HCV) and human immunodeficiency virus (HIV) continue to grow. The CDC recommends a one-time HCV screen for individuals in the Baby Boomer population (those born between 1945 and 1965) and a one-time HIV screen for all individuals between ages 13–64, with more frequent screening for both conditions based on individual risk factors. Methods: A system-wide electronic medical record alert prompting HCV screening was implemented in May 2016 targeting the Baby Boomer population. In addition to the system alert, an educational program detailing disease epidemiology, screening recommendations, and algorithms to guide screening efforts was developed by a quality improvement team to increase HCV and HIV screening and linkage to care for positive patients. Carolinas HealthCare System (CHS) is a nonprofit, vertically integrated healthcare system with approximately 12 million patient encounters per year. Twelve primary care practices, including 5 safety-net practices serving predominantly Medicaid and uninsured patients, with total of 43, 000 patients born between 1945 and 1965 were selected for the educational intervention. Results: Prior to the system-wide HCV alert, from May-December 2015, 2430 patients were screened for Hepatitis C; one year later post-HCV alert, from May-December 2016, 8872 patients were screened, resulting in a 350% increase in screening. Chi-squared analysis comparing the percentage of patients tested between the two- time periods was significantly different ( P = 0.001). For the educational intervention initiated in November 2016: average patient HCV testing over the 12 sites was 1480 per month before the intervention, and rose to 1713 per month post-education implementation ( P < 0.001). Similarly, for HIV testing: average patient HIV testing was on average 493 per month increasing to 621 average per month after the educational program ( P <  0.001) Conclusion: EMR modifications and provider education along with availability of connect to care partners within a large, integrated, healthcare system can significantly enhance screening and care for patients with HCV and HIV. Innovative interventions are needed to improve screening rates and link positive patients into care. Disclosures: All authors: No reported disclosures.